Settling of superparamagnetic silica encapsulated DNA microparticles in river water. Issue 1 (15th January 2023) - Tang, Yuchen; Zhang, Fengbo; Bogaard, Thom; Chassagne, Claire; Ali, Zeeshan; Bandyopadhyay, Sulalit; Foppen, Jan Willem
Abstract: Particle tracers are sometimes used to track sources and sinks of riverine particulate and contaminant transport. A potentially new particle tracer is ~200 nm sized superparamagnetic silica encapsulated DNA (SiDNAFe). The main objective of this research was to understand and quantify the settling and aggregation behaviour of SiDNAFe in river waters based on laboratory settling experiments. Our results indicated, that in quiescent conditions, more than 60% of SiDNAFe settled within 30 h, starting with a rapid settling phase followed by an exponential‐like slow settling phase in the three river waters we used (Meuse, Merkske, and Strijbeek) plus MilliQ water. In suspensions of 1000× higher particle concentrations, the hydrodynamic diameter ( D h‐DLS ) of SiDNAFe increased over time, with its polydispersity index (PDI) positively correlated with particle size. From these observations, we inferred that the rapid SiDNAFe settling was mainly due to homo‐aggregation and not due to hetero‐aggregation (e.g., with particulate matter present in river water). Incorporating a first‐order mass loss term which mimics the exponential phase of the settling in quiescent conditions seems to be an adequate step forward when modelling the transport of SiDNAFe in river injection experiments. Furthermore, we validated the applicability of magnetic separation and up‐concentration of SiDNAFe in real river waters, which is an important advantage for carrying out field‐scale SiDNAFe tracing experiments. Abstract : In three river waters and in MilliQ, more than 60% of SiDNAFe settled rapidly followed by an exponential‐like settling. Rapid settling was mainly due to homo‐aggregation. Incorporating a first‐order mass loss term which mimics the exponential phase of settling is a step forward in modelling transport of SiDNAFe in river injection experiments.